RANCANG BANGUN APLIKASI E-FACILITY PLANT BERBASIS LARAVEL DI PT PHILIPS INDUSTRI BATAM - Khisal; Saragih, Saut Pintubipar (Computer Science and Industrial Engineering, 2025)
This research addresses the challenges of conventional facility reporting and inspection at PT Philips Industri Batam, characterized by slow data access, limited real-time monitoring, and hindered decision-making. The primary objective was to design and develop an E-Facility web application utilizing Laravel and Filament to digitalize facility management and provide real-time monitoring capabilities. Employing a Research and Development (R&D) methodology , the study involved comprehensive analysis, system design (including UML modeling), implementation, and rigorous testing through Black Box and User Acceptance Testing. The research findings demonstrate significant improvements in operational productivity. Notably, login time reduced to 5 seconds, and data input time decreased from 1 minute to 10 seconds. Data accuracy significantly improved, with data availability transforming from hours of physical search to under 5 seconds. Furthermore, the system optimized resource utilization, leading to nearly zero paper usage for forms and reducing report generation time from hours to minutes. This indicates a potential 15-25% reduction in overall operational costs. In conclusion, the E-Facility application successfully digitalized the facility management process, offering an optimal, precise, and responsive solution in line with Industry 4.0 digitalization initiatives.